2006
DOI: 10.1515/hf.2006.035
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of wood with aminofunctional silanes for protection against wood destroying fungi

Abstract: Different aminofunctional silanes were tested for their suitability to preserve wood against basidiomycetes in a mini-block experiment according to EN 113. High effectiveness against the brown rot fungusConiophora puteanawas maintained over prolonged exposure times of up to 18 weeks. Resistance against the white rot fungusTrametes versicolorwas only enhanced in the initial phase of exposure (6 weeks); after longer exposure times of 18 weeks, considerable mass losses were observed. It was shown that the antifun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 11 publications
0
36
1
1
Order By: Relevance
“…Isquith et al (1972) demonstrated that the Si-Quat had antimicrobial activity in a serial tube dilution method without entering the cell and attributed this activity to membrane phenomena. Donath et al (2006b) proved the Si-Quat to be also effective in protecting Scots pine sapwood against fungal decay by C. puteana when incorporated in a siloxane matrix. The Si-Quat was applied at a concentration of at least 0.5% ai in combination with 5% ai multifunctional silane.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Isquith et al (1972) demonstrated that the Si-Quat had antimicrobial activity in a serial tube dilution method without entering the cell and attributed this activity to membrane phenomena. Donath et al (2006b) proved the Si-Quat to be also effective in protecting Scots pine sapwood against fungal decay by C. puteana when incorporated in a siloxane matrix. The Si-Quat was applied at a concentration of at least 0.5% ai in combination with 5% ai multifunctional silane.…”
Section: Discussionmentioning
confidence: 95%
“…It is not surprising that the leachates are toxic and it is clear that lower concentrations of IPBC would still be effective against decay and yield lower toxicity towards D. magna. Donath et al (2006b) have treated Scots pine and beech mini-blocks with a multifunctional silane alone or in 209p5 combination with 3-(trimethoxysilyl)propyldimethyloctadecyl ammonium chloride (Si-Quat). After EN 84 leaching the recorded mass losses were about the same irrespective the addition of the Si-Quat to the treating solutions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations